Kontroversi Sekitar Produk Fangan Hasil Rekayasa Genetika - Nurhayati Abbas (Jurnal Hukum IUS QUIA IUSTUM, 2003)
Genetically Modified Organism (GMO) is a relative new technology which applied toplants and cattle, to increase the quality of the food product But many things organism have not been known by the experts, that could make unpredictable denger to the humanbeing and the environment. Do the regulation as instrumentator testing and to control the spread of the food product which contain genetically modified organism technology, should be applied.